Christmas letters - Macomber, Debbie (Don Mills, Ont. : MIRA, 2006)
When Katherine O'Connor, who writes Christmas letters for other people, meets Dr. Wynn Jeffries, a child psychologist, at the French cafe on Blossom Street, their opposing viewpoints on raising children ruin Katherine's Christmas cheer.
Keywords: Women -- Washington (State) -- Fiction; Seattle (Wash.) -- Fiction